Earthquake Hazard Education and Disaster Preparedness Assessment among Senior High School 1 Wedi Students in Klaten Regency - Agung Hidayat; Prabang Setyono; Mohammad Masykuri; Siti Khoiriyah; Cynthia Permata Sari; Anggun Deristani; Zabilla Tomy Sanjaya (Prospect Publishing, 2026)
Indonesia is highly prone to earthquakes; therefore, improving disaster preparedness in schools is essential. This community service activity aimed to provide earthquake hazard education and a disaster preparedness assessment to students of Senior High School in Klaten Regency. The participants were 30 students who are members of the Adiwiyata School Cadre. The activity included an interactive socialization session discussing earthquake characteristics, regional vulnerability in Klaten, and mitigation measures at school and at home. After the session, students completed a 10-question questionnaire via Google Forms. The data were analyzed descriptively to assess students’ knowledge, attitudes, and preparedness behaviors. The results showed that the average preparedness score reached 88%. All students understood that Indonesia is an earthquake-prone country and were aware of appropriate actions after an earthquake and safety procedures when outdoors. Most students could also recognize early signs of earthquakes, understand the importance of evacuation routes and emergency preparedness kits, and identify the function of a seismograph. However, some students still had difficulty distinguishing between structural and non-structural mitigation. Overall, students of Senior High School in Wedi demonstrated good disaster preparedness. Strengthening contextual and sustainable disaster education in schools is therefore recommended.